GOVERNING WITHOUT AUTHORITY: MUNICIPAL BROKERAGE IN FRAGMENTED BLUE ECONOMY GOVERNANCE - Qurnia Indah Permata Sari; Ibnu Asqori Pohan; Fathul Bari; Bunga Qeila Anthea Anwar (GoAcademica Research dan Publishing, 2026)
This article examines how municipal governments exercise governance functions in implementing the blue economy when higher levels of government hold formal authority over marine space. Drawing on a qualitative case study of coastal Singkawang, Indonesia, the study analyzes how authority fragmentation shapes municipal action across fisheries services, administrative facilitation, fuel recommendation support, seafood value chain development, fish market coordination, marine waste management, and mangrove-based coastal initiatives. The findings show that although the municipal government has limited formal authority over marine areas, it remains a strategic actor because it is the closest public institution to fishers, traders, seafood processors, and coastal communities. The article develops the concept of municipal brokerage without authority to explain how local governments govern through facilitation, coordination, policy translation, and everyday problem-solving rather than through direct jurisdictional control. This concept contributes to the blue economy governance and multi-level governance literature by showing that authority fragmentation not only creates governance gaps but can also produce brokerage roles for municipal governments positioned close to local communities. The article argues that recognizing these brokerage functions is essential for designing more responsive, inclusive, and socially grounded blue economy policies in non-metropolitan coastal cities.